2012
DOI: 10.3389/fpsyt.2012.00038
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Chronic Ethanol Self-Administration on Hippocampal Serotonin Transporter Density in Monkeys

Abstract: Evidence for an interaction between alcohol consumption and the serotonin system has been observed repeatedly in both humans and animal models yet the specific relationship between the two remains unclear. Research has focused primarily on the serotonin transporter (SERT) due in part to its role in regulating extracellular levels of serotonin. The hippocampal formation is heavily innervated by ascending serotonin fibers and is a major component of the neurocircuitry involved in mediating the reinforcing effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 81 publications
2
12
0
Order By: Relevance
“…Now these tissues and associated bioinformatics are widely available to the larger alcohol research community through the interactive MATRR website. Since its inception, the MATRR has contributed resources that have been cited in 70 peer-reviewed publications, including reports of the functional (Ariwodola et al, 2003; Budygin et al, 2003; Floyd et al, 2004; Alexander et al, 2006; Carden et al, 2006; Anderson et al, 2007; Cuzon-Carlson et al, 2012; Welsh et al, 2011), genomic (Hemby et al, 2006; Acosta et al, 2009; Burnett et al, 2012), proteomic (Freeman et al, 2006, 2010, 2011), biochemical (Ivester et al, 2003; 2007; Lebold et al, 2010) and cardiac (Cheng et al, 2010) consequences of long-term, excessive ethanol consumption. The pathophysiological effects of chronic EtOH on the hypothalamic-pituitary-adrenal axis have also been well-characterized (Morrow et al, 2006; Porcu et al, 2006a, b, 2010; Ferguson et al, 2012; Helms et al, 2012a, b, c, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Now these tissues and associated bioinformatics are widely available to the larger alcohol research community through the interactive MATRR website. Since its inception, the MATRR has contributed resources that have been cited in 70 peer-reviewed publications, including reports of the functional (Ariwodola et al, 2003; Budygin et al, 2003; Floyd et al, 2004; Alexander et al, 2006; Carden et al, 2006; Anderson et al, 2007; Cuzon-Carlson et al, 2012; Welsh et al, 2011), genomic (Hemby et al, 2006; Acosta et al, 2009; Burnett et al, 2012), proteomic (Freeman et al, 2006, 2010, 2011), biochemical (Ivester et al, 2003; 2007; Lebold et al, 2010) and cardiac (Cheng et al, 2010) consequences of long-term, excessive ethanol consumption. The pathophysiological effects of chronic EtOH on the hypothalamic-pituitary-adrenal axis have also been well-characterized (Morrow et al, 2006; Porcu et al, 2006a, b, 2010; Ferguson et al, 2012; Helms et al, 2012a, b, c, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…For example, ETOH is known to affect 5-HTT expression (Burnett, Davenport et al 2012) and to inhibit 5-HT clearance in a 5-HTT-independent manner (Daws, Montanez et al 2006). We have previously shown that Tph2KI mice do not have significant alterations in 5-HTT expression in the brainstem, hippocampus, striatum or frontal cortex (Beaulieu, Zhang et al 2008), and thus, we do not believe that differences in 5-HTT function are responsible for any of the observed phenotypes of these animals.…”
Section: Discussionmentioning
confidence: 99%
“…The subjects and ethanol self-administration methods used in the current study have been described in detail previously (Burnett et al, 2012). Nine individually housed adult male cynomolgus macaques ( Macaca fascicularis ) voluntarily self-administered ethanol, water and banana flavored food pellets (Research Diets Incorporated, New Brunswick, NJ) 22 hr/day for 12 months using an operant panel permanently attached to their home cage.…”
Section: Methodsmentioning
confidence: 99%